Temporal variation in habitat quality shapes the distribution–abundance relationship in waterbirds at landscape scale - Constantinos Charalambous; Petr Musil; Mathilde Legoguelin; Zuzana Musilová; David Hořák (Ecosphere)
Abstract The distribution–abundance relationship (DAR) is a well‐established macroecological pattern, where more locally abundant species are also more widespread across landscapes. However, it is not clear whether this relationship is temporally invariant, or how destabilization may manifest. Here, we examine the DAR at the landscape level in a unique but overlooked model system, that is, a waterbird assemblage inhabiting fishponds within the Třeboňsko Basin Biosphere Reserve, Czechia. Using 12 years of biannual census data across 134 intensively managed fishponds, collected in May and July, we describe variation in the slope of the DAR, expressed as the association between bird density and fishpond occupancy. We then tested for the role of environmental parameters and bird traits in determining the relationship's shape, utilizing general multivariate regression and a model‐averaging technique. Overall, we corroborated an expected positive DAR for waterbirds, and we present, for the first time, a consistent seasonal weakening of the interspecific DAR. We posit that this decline in the relationship's slope is a result of the deterioration and homogenization of habitat quality later in the summer, which resulted in a large deficit of suitable fishponds as populations increased. The DAR did not vary among years in either month. We also found that population trend was the most influential predictor of each species' response to changing environmental conditions; species with increasing regional abundance have stronger intraspecific DARs. Our results show that seasonal deterioration of habitat quality significantly impacts waterbird communities by altering the population spatial structure and that this is reflected in the shape of the DAR. This finding has important practical consequences, particularly in landscapes under human exploitation, where management decisions can determine ecosystem structure. Such analytical approaches can be used to pinpoint processes that are difficult to detect otherwise and thus assist conservation efforts.